Pengaruh Kualitas Layanan terhadap Kepuasaan Pengguna Badan Layanan Umum (BLU) Bidang Pendidikan Universitas selama Pandemi Covid-19 - Benediktus Tandya Pinasthika; Alhamdi Zuhri; Martdian Ratna Sari (Journal of Management and Business Review, 2023)
This study examines the effect of service quality on user satisfaction of public service agencies (BLU) in the education sector during the covid-19 pandemic. The quality of the services is measured using 14 service satisfaction indicators released in the Decree of the Minister of Administrative Reform Number: 63/KEP/M.PAN/7/2003. The sample in this research is state universities (PTN) with legal entities in Jabodetabek. The sample was determined using a purposive sampling technique. The results of this study indicate that service quality has a positive effect on service user satisfaction. Therefore, the better the service quality, the higher the satisfaction of service users.